Spirituality and Medicine: A Workshop for Medical Students and Residents - Barnett, Katherine Gergen (Blackwell Science Inc, 2006)
INTRODUCTION: Governing bodies for medical education recommend that spirituality and medicine be incorporated into training. AIM: To pilot a workshop on spirituality and medicine on a convenience sample of preclinical medical students and internal medicine residents and determine whether content was relevant to learners at different levels, whether preliminary evaluation was promising, and to generate hypotheses for future research. SETTING: Private medical school and university primary care internal medicine residency program, both in the Northeast. CURRICULUM DESCRIPTION: The authors designed and implemented a required 2-hour workshop for all second-year medical students and a separate required 1.5-hour workshop for all primary care internal medicine house staff. The workshops used multiple educational strategies including lecture, discussion, and role-play to address educational objectives. PROGRAM EVALUATION: Learners completed optional, anonymous pre and postworkshop surveys with six 5-point Likert-rated statements and space to cite the most useful part of the curriculum and their remaining questions. One hundred and thirty-seven learners participated and 100 completed both surveys. Medical students and residents had increased (all P≤.002): agreement regarding the appropriateness of inquiring about spiritual and religious beliefs in the medical encounter, their perceived competence in taking a spiritual history, and their perceived knowledge of available pastoral care resources. Medical students, but not residents, had an increase in their perceived comfort in working with hospital chaplains. DISCUSSION: A brief pilot workshop on spirituality and medicine had a modest effect in improving attitudes and perceived competence of both medical students and residents.